Transcatheter atrial septal defect closure: Focus on tips and tricks for interventional procedure in challenging cases - Setiawan, Dion; Putri, Valerinna Yogibuana Swastika; Martini, Heny; Karolina, Wella (Universitas Brawijaya, 2025)
The ostium secundum defect is the most prevalent form of atrial septal defect (ASD). The development and refinement of devices and techniques for transcatheter ASD closure have led to its acceptance as the preferred management for most patients with secundum ASD. Meticulous planning and execution constitute the key to achieving success in a procedure. It entails a thorough assessment of the patient, beginning with selecting suitable cases, as well as detailed pre- and intraprocedural imaging, knowledge of various device deployment techniques, anticipation of potential complications, and appropriate management strategies. This review article will discuss tips and tricks to overcome the technical intricacies of achieving a successful transcatheter ASD closure and address some challenging cases associated with its use.